Strona i inni uczestnicy postępowania w sprawie wydania pozwolenia na budowę w świetle ostatnich zmian ustawowych - Ziety, Jakub (PRAWO i WIĘŹ, 2025)
The subject of the article is an analysis of the changes in the construction law concerning the parties to the procedure for obtaining a construction permit. The legislator has limited the scope and conditions of recognition as a party to the above procedure. However, due to the need to implement the provisions of EU directives, it was necessary to expand the circle of entities authorised to file appeals or complaints with administrative courts for participants in proceedings on the issue of environmental decisions and ecological organisations. These entities have the status of participants in appeal proceedings with the rights of a party. However, the scope of the allegations in the appeal was limited to non-compliance of the construction permit decision with the issued environmental decision. If the appeal contains other allegations, the second-instance authority must reject or discontinue the proceedings.